The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.21203/rs.3.rs-23855/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Levels, Trends and Determinants of Technical Efficiency of General Hospitals in Uganda: Data Envelopment Analysis and Tobit Regression Analysis

Abstract: Background: General hospitals provide a wide range of primary and secondary healthcare services. They accounted for 38% of government funding to health facilities, 8.8% of outpatient department visits and 28% of admissions in Uganda in the financial year 2016/17. We assessed the levels, trends and determinants of technical efficiency of general hospitals in Uganda from 2012/13 to 2016/17. Methods: We undertook input-oriented Data Envelopment Analysis to estimate technical efficiency of 78 general hospitals usi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…Among evaluated variables, three were associated with e ciency, two of which lead to decreased e ciency. The number of health technicians was associated with decreased e ciency, there ndings were consistent with the study of Ayiko R et al, and further proof that the surplus of professional and technical personnel will lead to ine ciency 45 . In addition, the results of Tobit regression found that the building business room area of regional MCH institutions was related to the low e ciency, which was consistent with the results of Aleksandar et al 40 .…”
Section: Discussionsupporting
confidence: 87%
“…Among evaluated variables, three were associated with e ciency, two of which lead to decreased e ciency. The number of health technicians was associated with decreased e ciency, there ndings were consistent with the study of Ayiko R et al, and further proof that the surplus of professional and technical personnel will lead to ine ciency 45 . In addition, the results of Tobit regression found that the building business room area of regional MCH institutions was related to the low e ciency, which was consistent with the results of Aleksandar et al 40 .…”
Section: Discussionsupporting
confidence: 87%
“…The second regressor was average length of stay (ALOS) [ 70 , 71 ]. The third regressor was teaching status (Teach), a dummy variable that represents whether a hospital is attached to a university [ 72 ]. The fourth regressor was type of hospital [ 21 ], another dummy variable that explains whether a structure is labeled a HUB hospital.…”
Section: Methodsmentioning
confidence: 99%